A Theory of Change to grow numbers of African rhino at a conservation site. Issue 6 (23rd April 2019) - Balfour, Dave; Barichievy, Chris; Gordon, Chris; Brett, Rob
Abstract: Rhino horn is highly valued and this drives the illegal hunting of rhino. As a strategy to counter rhino losses incurred through poaching, managers of African protected areas face pressure to increase the number of rhino in their populations by promoting their growth. These efforts are commonly constrained by being balanced against other protected area objectives which seek to manage toward a "natural ecological state". This is reflected in the draft continental rhino conservation plan as well as many national‐level rhino plans in Africa, but details on how this can be achieved at a site level are limited; indeed a framework for thinking about the problem is lacking. Here we develop a Theory of Change (ToC) which guides management interventions when seeking to grow rhino numbers at a conservation site. We identify four thematic areas for intervention namely; habitat management; range availability; containment and natural attrition; and rhino population management. As many protected areas are underfunded they seek to attract funding, but many donors are uncertain as to best practice and/or are hesitant to dictate how funds should be spent. This ToC can serve as a framework to guide funding. It can also guide policy in this regard.